Pengenalan dan Pelatihan Literasi Digital pada Generasi Milenial - Yetty Yetty; Abi Suar; Abdurrahman Senuk; Firdaus Duko (Universitas Kristen Indonesia Toraja, 2024)
Digital literacy for students can be an obstacle in finding information circulating, especially if they cannot filter the information circulating. Therefore, a digital literacy culture in schools is very important to prevent them from negative things obtained from social media. The role of teachers as educators is also very important, so they must be able to become leaders in mobilizing this literacy. The PKM method used is an introduction and training approach. Target achievements (1) This PKM program is able to provide an in-depth understanding of Digital Literacy. community service results Digital literacy training is an important step in increasing understanding in the millennial generation of digital technology. This is the main component that was successfully implemented in this PKM. In addition, this training also helps in the implementation of learning digitization.